The spirit of 1896 a mirror of the Philippine past, a window on the nation's future - Co, Jason (Centennial literary prize series., 2000)
'The journey of a thousand miles starts with the first step. For the Filipino nation, that first step was the Revolution of 1896 and the founding of Asia's first free Republic. Even today's Filipinos are born with the ideals and the spirit of a people who had lost—then regained—their faith; a people who have struggled, suffered defeat, and survived it. And now it is time to remember the incredible sacrifice and courage that went into molding the congeries of Philippine tribes into one nation.'--Publisher.